Analysis of radio wave propagation in an urban environment and its application to initial disaster response support - Kawamura, Y.; Jang, Hyong Doo; Wagner, M.; Nobuhara, H.; Dewan, Ashraf; Veenendaal, Bert; Kitahara, I. (Fuji Technology Press, 2015)
When disasters strike, it is important to quickly collect and analyze disaster-related information immediately after the event. We have suggested ZigBee and geographic information systems (GIS) technologies to resolve these problems and provide an effective communications system. In this paper, a method for the rapid setup of short-range wireless networks infrastructure, which estimates the radio wave propagation and optimizes the positions of transmitters is proposed. Our estimation method is experimentally verified, and it combines ray-tracing with preliminarily obtained statistical attenuation information, which allows us to consider different types of the land and its elevation. Thus, we can determine the effective ranges for radio communication for each potential location in the actual environment. This information is then used in our optimization procedure to reduce the number of transmitters needed to establish connections.